Critical Success Factors of Retail and Wholesale Industry: A Case Study - Jaafar, Jimisiah; Kamarul Zaman, Nur Tasnim; Adtrudin, Khairul Firdaus; Hasan, Sallaudin; Salleh, Mohd Mansor (International Journal of Supply Chain Management, 2016)
This paper illustrate to identify critical success factors of retail and wholesale industry base on a case study. The rampant development of urban advancement in Malaysia has expanded the quantity of basic supply retail outlets that gives assortments of items. Due to this, clients are accustomed to visit different oulets. Retailer also acknowledged consumer loyalty playing a part in their business achivement. Therefore, it has become inportant for grocery retail stores to identify the factors in decision makings of customer selections. This study was conducted in three chosen stores, specifically Mydin, Giant and Tesco in Alor Star, Kedah, Malaysia. Data from 190 respondents were collected from questionnaires. Daya will than analysed by using summative score examination, relative investigation and chi-square freedom test. Primary variables that were significant were location, facility, process, product quality and value of money.Hence, a few suggestion are displayed to enhance consumer loyalty and dependability of their clients. This study unlocks further frontiers for the prospective entrepreneur in order to get idea about various success factors to set up retail business. With this study it also contribute for sustainability of the business retail and wholesale outlet.